Pembuatan Mural Islami Sebagai Sarana Edukasi Pada Pesantren Taruna Alqolam - Sungguh Ponten Pranata; Husriani Husain (Pusat Riset dan Inovasi Nasional, 2022)
Taruna Alqolam Islamic Boarding School carries out community service by holding mural-making activities on the Islamic boarding school's walls to spread important messages to the surrounding community. The murals created by the students function as decoration and as a reminder of the importance of environmental cleanliness, local wisdom, and religious values. Through this service, the students also provide knowledge and skills to the surrounding community and strengthen ties between the Islamic boarding school and the local community. Discussion of the results of the service opens up space for in-depth reflection on the values ​​contained in the work of art and how these messages can permeate people's daily lives. Taruna Alqolam Islamic Boarding School has created an environment that promotes sound values, increases awareness of important issues, and inspires behavior under religious and moral teachings. Thus, this service benefits the surrounding community and provides valuable experience for the students in terms of contributing to society and strengthening the role of Islamic boarding schools in building a better and more sustainable society socially, environmentally, and spiritually.